The Economy of Wellbeing in Beji: Pesantren and Entrepreneurship in Village Community - Syamsul Hadi (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2019)
This article aims to explain the field findings related to the socio-economic conditions of the community in Beji village. The village was known as the base of the santri and the socio-economic impacts that provide value to the life of the community around the pesantren. The research used a qualitative method with a constructivism approach. Excavation of data through in-depth interview techniques and field observations and enriched with document studies. Informants interviewed were determined through the snowballing techniques. The result of the research shows that the existence of Manbail Futuh pesantren in the middle of village society not only serves to serve religious education (Islam) but with the number of santri coming from various regions, so the existence of pesantren also gives a socio-economic impact for the surrounding community. Against the community the economic benefits provided by pesantren is not active but passive. This is because the pesantren is limited to providing opportunities for local residents in the pesantren location to accommodate 833 students of mukim and has an active student of 2,469 people without attracting any pennies for